2013
DOI: 10.3810/pgm.2013.11.2710
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Microbiologic Epidemiology of Community-Acquired Pneumonia

Abstract: Community-acquired pneumonia (CAP) is a common infectious disease in the United States and the incidence continues to grow as the aging population increases. Overall, in-hospital patient mortality rates have been reported to be as high as 18%. Management of patients with CAP has been challenged by the evolution of resistant pathogens (particularly Streptococcus pneumoniae and Staphylococcus aureus) that have reduced susceptibility to recommended standard antimicrobial agents. Streptococcus pneumoniae continues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 90 publications
(153 reference statements)
0
17
1
1
Order By: Relevance
“…real-time reversetranscriptase polymerase chain reaction) has revealed a very different picture. Nowadays viral etiologies per se are responsible for one-third of all cases of communityacquired pneumonias (CAP) [62,63]. These etiologies include influenza, parainfluenza, coronavirus, rhinovirus, metapneumovirus, adenovirus, respiratory syncytial virus, and other less frequent microorganisms.…”
Section: Role Of Viral-bacterial Co-infections and Their Effect On Oumentioning
confidence: 99%
“…real-time reversetranscriptase polymerase chain reaction) has revealed a very different picture. Nowadays viral etiologies per se are responsible for one-third of all cases of communityacquired pneumonias (CAP) [62,63]. These etiologies include influenza, parainfluenza, coronavirus, rhinovirus, metapneumovirus, adenovirus, respiratory syncytial virus, and other less frequent microorganisms.…”
Section: Role Of Viral-bacterial Co-infections and Their Effect On Oumentioning
confidence: 99%
“…Community‐acquired pneumonia (CAP) has been associated with significant mortality among hospitalized patients . Appropriate antibiotic treatment is challenged by the emergence of resistant strains, including those of Streptococcus pneumoniae . Treatment recommendations are based on randomized controlled trials (RCTs) comparing monotherapy regimens in hospitalized patients with low mortality probability and on observational studies evaluating more severely ill patients than those enrolled in RCTs .…”
Section: Introductionmentioning
confidence: 99%
“…1 Appropriate antibiotic treatment is challenged by the emergence of resistant strains, including those of Streptococcus pneumoniae. 2,3 Treatment recommendations 1,[4][5][6][7][8][9] are based on randomized controlled trials (RCTs) comparing monotherapy regimens in hospitalized patients with low mortality probability and on observational studies evaluating more severely ill patients than those enrolled in RCTs. 10,11 Monotherapy and combination regimens are recommended for mild or moderate CAP; combination regimens are mainly recommended for severe CAP.…”
Section: Introductionmentioning
confidence: 99%
“…The most common pathogens implicated in pneumonia are Streptococcus pneumoniae, Mycoplasma pneumoniae, Chlamydia pneumoniae, Haemophilus influenzae, Legionella species, and respiratory viruses. 19,20 In addition, multiple studies have shown Staphylococcus aureus to be one of the most common pneumonia pathogens behind S pneumoniae. 21 Regarding HAP, the largest report on the microbiology of HAP showed that most culture-positive cases were due to S aureus and gramnegative pathogens.…”
Section: What Pathogens Are Responsible For Causing Pneumonia?mentioning
confidence: 99%